2019
DOI: 10.1371/journal.pone.0219902
|View full text |Cite
|
Sign up to set email alerts
|

Eight-year trajectories of changes in health-related quality of life in knee osteoarthritis: Data from the Osteoarthritis Initiative (OAI)

Abstract: Background Knee osteoarthritis (OA) worsens health-related quality of life (HRQoL) but the symptom pathway varies from person to person. We aimed to identify groups of people with knee OA or at its increased risk whose HRQoL changed similarly. Our secondary aim was to evaluate if patient-related characteristics, incidence of knee replacement (KR) and prevalence of pain medication use differed between the identified HRQoL trajectory groups. Methods Eight-year follow-up d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 37 publications
7
31
1
3
Order By: Relevance
“…Due to the confluence of the increasing prevalence of risk factors such as obesity, aging, and joint injuries, the incidence and prevalence of osteoarthritis are also rising (Hunter and Bierma-Zeinstra, 2019). Symptoms may include severe pain, stiffness, and instability in the affected joint/s (Stark and Price, 2019;Törmälehto et al, 2019). Because there is no known cure and symptoms tend to worsen in severity over time, osteoarthritis can have a progressively debilitating impact on an individual's health and functioning (Hunter and Bierma-Zeinstra, 2019;Törmälehto et al, 2019), particularly when conservative management interventions are unsuccessful in restricting disease progression (Jones et al, 2007;O'Brien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the confluence of the increasing prevalence of risk factors such as obesity, aging, and joint injuries, the incidence and prevalence of osteoarthritis are also rising (Hunter and Bierma-Zeinstra, 2019). Symptoms may include severe pain, stiffness, and instability in the affected joint/s (Stark and Price, 2019;Törmälehto et al, 2019). Because there is no known cure and symptoms tend to worsen in severity over time, osteoarthritis can have a progressively debilitating impact on an individual's health and functioning (Hunter and Bierma-Zeinstra, 2019;Törmälehto et al, 2019), particularly when conservative management interventions are unsuccessful in restricting disease progression (Jones et al, 2007;O'Brien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no known cure and symptoms tend to worsen in severity over time, osteoarthritis can have a progressively debilitating impact on an individual's health and functioning (Hunter and Bierma-Zeinstra, 2019;Törmälehto et al, 2019), particularly when conservative management interventions are unsuccessful in restricting disease progression (Jones et al, 2007;O'Brien et al, 2019). Patients with end-stage osteoarthritis experience considerable pain, as well as functional limitations in relation to mobility, activities of daily living, independence, and occupational and social participation (Neogi, 2013;O'Brien et al, 2019;Törmälehto et al, 2019). Symptoms can lead to disrupted sleep and fatigue (Sasaki et al, 2014a), and reliance on a caregiver (Hunter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent, larger survey, data from 3053 individuals in the Osteoarthritis Initiative (OAI) study reported the presence of at least mild knee pain in 67.1%. [11] African Americans are most likely to report knee pain. Serial surveys data from the National Health and Nutrition Examination Survey and Framingham Osteoarthritis study suggest that the prevalence of knee pain in the US has increased by 65% between 1983 and 2005, with non-Hispanic Blacks more likely to report knee pain [12].…”
Section: Introductionmentioning
confidence: 99%